2011
DOI: 10.1093/ndt/gfr055
|View full text |Cite
|
Sign up to set email alerts
|

Patient attitudes towards the arteriovenous fistula: a qualitative study on vascular access decision making

Abstract: AVF refusal is multifactorial and depends on individual patients. Although nephrologists consider the fistula to be the optimal VA, patients do not think in the same terms of reducing infection rates but focus on the practical day-to-day use of their VA and its influence on their quality of life and future outlook.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
103
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 28 publications
2
103
0
3
Order By: Relevance
“…To understand the barriers that may have prevented patients from getting a transplant had they been medically suitable, we deliberately included patients who may have been unsuitable for transplant. Moreover, their attitudes may have influenced others who were medically suitable (17)(18)(19). Severe PVD is a relative contra-indication to transplantation at our center and a known predictor of morbidity and mortality in ESRD (29), which may explain why these patients were less likely to want LDKT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the barriers that may have prevented patients from getting a transplant had they been medically suitable, we deliberately included patients who may have been unsuitable for transplant. Moreover, their attitudes may have influenced others who were medically suitable (17)(18)(19). Severe PVD is a relative contra-indication to transplantation at our center and a known predictor of morbidity and mortality in ESRD (29), which may explain why these patients were less likely to want LDKT.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all patients were eligible to participate in the study, regardless of their candidacy for kidney transplantation. We reasoned that the concerns and attitudes of both potentially eligible and ineligible LDKT candidates might help us develop targeted interventions designed to increase LDKT rates among black women and alleviate some existing disparities (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, only 24% of patients had no preference; 12% preferred a CVC (nonblack women had the highest CVC preference at 17%). The most common reasons for preferring a CVC were no puncture and no bleeding, avoidance of disfigurement, and better cosmesis (51,54). The DOPPS survey revealed that up to 20% of patients received little or no vascular accessrelated education, suggesting that they did not fully understand the risks and benefits of various vascular access types.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…A qualitative study conducted among 13 Canadian hemodialysis patients who had elected to receive chronic dialysis via a catheter identified adverse personal or vicarious experience with a fistula related to cannulation, bleeding, time commitment, and/or appearance as factors driving this decision. 17 Others expressed a desire to maintain the status quo even when they understood the risks associated with catheter use.…”
mentioning
confidence: 99%
“…16,17 And even in situations where fistula placement would clearly be beneficial, older adults with advanced kidney disease (who often have a variety of other health conditions) may need to prioritize other, more pressing health concerns over fistula placement. 18,19 Patients may themselves be uncertain about whether they would want dialysis should the need arise and may be unwilling to undergo fistula or even graft placement when there are so many unknowns.…”
mentioning
confidence: 99%